Escola e vida: influ??ncias da escola para as trajet??rias sociais de jovens egressos do ensino m??dio - Baciano, Gislaine de Medeiros (2015)
School and life: school influences to the social trajectories of young graduates high school addresses the social experiences of high school graduates young people, trying to understand the school's influences for your design. It would be high school responsible for the social destination of young people? This was the problem that provoked the development of this research. To reflect on the issue, first was carried a literature review on the Bank of Theses of Higher Education Personnel Improvement Coordination (CAPES), which were located few studies about high school graduates. The selected surveys, generally, deal with the school's contribution to the inclusion in higher education or in the labor market. Based on these data, I realized a survey in the approach favored high school graduates. Intended to analyze the social experiences of young people who had studied in various conditions and currently occupy different social positions. For this approach young people were selected from 18 to 29 years who had completed high school, based on three criteria: work, study and free time. In each of these conditions, the intention was to address young people in prestigious social situation and young people in a precarious social situation. From these criteria I defined six groups: engineers and marketers; students in a very disputed public university and students of a private university of easy access; youth in free time by choice (public park) and youth in free time for lack of choice (unemployment). A questionnaire with 64 questions predominantly open was applied with focus on the family , childhood , home, socioeconomic status , school, training and work. Then a young people of each group was interviewed, aiming to perform the analysis of life stories. In many cases, the economic and cultural capital families end up becoming educational capital, they allow children to acquire it. But when families are deprived of economic and cultural resources and/ or fail to invest in studies of children, or don???t promote their self-esteem these tend to have school, social and professional trajectories precarious. The life stories analyzed showed that the economic and cultural capital along with psychosocial support of the families, who invested in promoting self-esteem and the acquisition of educational and cultural capital for the children; and the subjectivity of young person in order to manage the multiple logics of action, develop their strategies, build their future projects and seek to carry them beyond the standard of occupational insertion and position in the home appear as the determining factors on youth social experiences.